Pemberdayaan masyarakat melalui penumbuhkembangan polindes bagi masyarakat miskin di pedesaan - Ristrini Wasis Budiarto (Berita Kedokteran Masyarakat (BKM), 2004)
Background and Method: The objective of this study is the community empowerment through the development of polindes for the poor community in villages in the framework of making pregnancy safer. The samples are selected purposively; there are Kupang Regency and Timor Tengah Selatan (TTS) and Ponorogo Regency. Two poor sub districts are selected from each regency and from each sub district ten or less village delivery house (polindes) are selected. Data collection is conducted through structured interview and FGD. The unit of analysis in this research is polindes and the analysis is conducted descriptively Results and Conclusion: The results show that most polindes is manned by a village midwife. The condition of the facility was clean but the equipment was insufficient and some polindes do not have a midwife kit. The medicines in polindes did not meet the standard and most or all of the polindes expenses was the responsibility of the government. Many people mentioned polindes as village clinic. Some have already known the real function of polindes. The village midwives are considered as competent but most of the patients in polindes are free from any fee, and if they have to pay, the fee is very cheap. Keywords: community empowerment, village delivery house (polindes), making pregnancy safer